Does Early Surgical Decompression in Cauda Equina Syndrome Improve Bladder Outcome?. Issue 8 (15th April 2015) - Srikandarajah, Nisaharan; Boissaud-Cooke, Matthew Alexander; Clark, Simon; Wilby, Martin John
<x xml:space="preserve">Abstract</x> Study Design. We analyzed retrospectively whether early surgery for cauda equina syndrome (CES) within 24, 48, or 72 hours of onset of autonomic symptoms made any difference to bladder function at initial outpatient follow-up. Objective. CES potentially causes loss of autonomic control including bladder dysfunction, resulting in significant disability. There is significant debate regarding appropriate timing of surgery. Summary of Background Data and Methods. We conducted a retrospective cohort study of 200 patients between 2000 and 2011 who underwent decompressive surgery for CES at a regional neurosurgical center. Data collected were from clinical admission and at initial follow-up. Presentation was categorized into CES with retention (CESR) and incomplete CES (CESI) and duration of autonomic symptoms before surgical intervention. Results. A total of 200 patients had complete clinical records; 61 cases with CESR and 139 cases with CESI. Average initial follow-up time was 96 days. For the 36 cases with CESI less than 24 hours, normal bladder function was seen at follow-up in all patients except 4 (11.1%), but with 103 cases with CESI more than 24 hours, 48 (46.6%) had bladder dysfunction (Pearson χ2P = 0.000). For the 64 cases with CESI less than 48 hours, normal bladder function was seen at follow-up in all except 10 (15.6%), but with 75 cases with CESI more than 48 hours, 42 (56%) had bladder dysfunction (Pearson χ2P = 0.000). For the 35 patients with CESR, operating within 24, 48, or 72 hours made no obvious difference to bladder outcome. Data were also reanalyzed changing the dataset groups to CESI less than 24 hours, 24 to 48 hours, and more than 48 hours to calculate odds ratios regarding normal bladder outcome. Conclusion. We identified that decompressive surgery within 24 hours of onset of autonomic symptoms in CESI reduces bladder dysfunction at initial follow-up, but no statistically significant difference in outcome was observed in CESR regarding timing of operation. Level of Evidence: 3